A Nationwide Study of Skiing and Snowboarding-Related Facial Trauma. Issue 1 (March 2022) - Sorenson, Thomas J.; Borad, Vedant; Schubert, Warren
Study Design: Retrospective descriptive observational study. Purpose: Skiing and snowboarding offers valuable opportunities for outdoor physical activity throughout the cold winter months, but these activities can result in substantial personally injury. This study aimed to analyze trends in skiing and snowboarding-related facial trauma epidemiology. Methods: The National Electronic Injury Surveillance System (NEISS) was queried for facial trauma related to skiing and snowboarding treated in United States (US) emergency departments between 2010 and 2019. These data and weighted estimates were used to analyze patient demographics, injury location, and etiology. Results: A total of 361 skiing or snowboarding-related facial injuries were recorded. Lacerations were most common injury (165/361; 45.7%), and facial fractures occurred in 21.6% (78/261) of patients. The most common facial fracture locations are the nose (38/78; 48.7%), orbit (17/78; 21.8%), and mandible (15/78; 19.2%). Pediatric patients accounted for 52% (187/361) of these injuries and had higher rates of lacerations (51.9% vs 39.1%, P < 0.05) and hospital admission (4.8% vs 1.15%, P < 0.05) than adults. Adults had a higher rate of facial fracture (30% vs 13.9%, P < 0.001) than children. Conclusions: Skiing and snowboarding-related facial trauma is relatively uncommon in the US. In general, these injuries are largely decreasing, but facial fractures still occur not infrequently during these activities. Based on our data, we strongly urge helmet manufacturers to increase the availability of recreational snowsport helmets that include nose, orbit, and mandible protections, which could help to prevent many of these injuries.